Processing of native and foreign language subtitles in films: an eye tracking study - Bisson, Marie-Josée; van Heuven, Walter J.B.; Conklin, Kathy; Tunney, Richard J. (Cambridge University Press, 2014)
Foreign language (FL) films with subtitles are becoming increasingly popular, and many European countries use subtitling as a cheaper alternative to dubbing. However, the extent to which people process subtitles under different subtitling conditions remains unclear. In this study, participants watched part of a film under standard (FL soundtrack and native language subtitles), reversed (native language soundtrack and FL subtitles), or intralingual (FL soundtrack and FL subtitles) subtitling conditions while their eye movements were recorded. The results revealed that participants read the subtitles irrespective of the subtitling condition. However, participants exhibited more regular reading of the subtitles when the film soundtrack was in an unknown FL. To investigate the incidental acquisition of FL vocabulary, participants also completed an unexpected auditory vocabulary test. Because the results showed no vocabulary acquisition, the need for more sensitive measures of vocabulary acquisition are discussed. Finally, the reading of the subtitles is discussed in relation to the saliency of subtitles and automatic reading behavior.